1980
DOI: 10.1099/00221287-119-2-287
|View full text |Cite
|
Sign up to set email alerts
|

Transformation in Micrococcus radiodurans: Measurement of Various Parameters and Evidence for Multiple, Independently Segregating Genomes per Cell

Abstract: Transformation frequencies greater than 1 % for some single markers were obtained in Micrococcus radiodurans when bacteria in the exponential phase of growth were resuspended in fresh growth medium containing 0.03 M-Ca2+ before being incubated with transforming DNA. Mg2+, Sr2+ or Zn2+ could not replace Ca2+ in giving high frequencies of transformation. The time required for the maximum expression of transformed markers was 2 to 3 h for resistance to rifampicin and acriflavin and 6 to 8 h for resistance to eryt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…This study began with the intent of identifying irrE. To accomplish this task, we took advantage of the D. radiodurans genome sequence and the efficiency of natural transformation in this species (28). A cosmid library generated from D. radiodurans R1 genomic DNA was transformed into competent IRS24 cultures and screened for clones capable of restoring ionizing radiation resistance to the strain.…”
Section: Discussionmentioning
confidence: 99%
“…This study began with the intent of identifying irrE. To accomplish this task, we took advantage of the D. radiodurans genome sequence and the efficiency of natural transformation in this species (28). A cosmid library generated from D. radiodurans R1 genomic DNA was transformed into competent IRS24 cultures and screened for clones capable of restoring ionizing radiation resistance to the strain.…”
Section: Discussionmentioning
confidence: 99%
“…Its cells are competent throughout the exponential growth stage. The frequency of transformants falls only during stationary phase (448,620), whereas other bacteria have maximal competence just before they enter stationary phase (509). CaCl 2 (30 mM) increases the frequency of transformation 40 times, with marker-specific efficiencies ranging from 0.01 to 3% (620).…”
Section: Genetics Of D Radioduransmentioning
confidence: 99%
“…The frequency of transformants falls only during stationary phase (448,620), whereas other bacteria have maximal competence just before they enter stationary phase (509). CaCl 2 (30 mM) increases the frequency of transformation 40 times, with marker-specific efficiencies ranging from 0.01 to 3% (620). A family of 13 proteins that are homologous to the putative nuclease inhibitor DinB in B. subtilis (50,232,380) may enhance the transformation proficiency of D. radiodurans.…”
Section: Genetics Of D Radioduransmentioning
confidence: 99%
“…1A). Since the Rif' point marker used is the most efficiently transformed marker discovered to date (21), the equally high level of efficiency of transformation to MMC resistance by using either wt or strain 112 genomic DNA suggests that the rec30 defect is due to a single mutation and, furthermore, that the rec30 mutation is not closely linked with the 112 defect. Two rec30 MMC-resistant isolates, one transformed by wt genomic DNA (30/wt) and one transformed by strain 112 genomic DNA (30/1), were found to be wt in all respects, including efficient natural transformation (Fig.…”
mentioning
confidence: 99%
“…The most studied of these species, Deinococcus radiodurans, was found to be naturally transformable by Moseley and coworkers, who showed that this organism is always competent during the exponential phase without manipulation and provided evidence, by using unlinked markers, for a minimum of four independently segregating genomes per cell (13,21). The latter observation is consistent with evidence based on renaturation kinetics (5) and pulsed-field gel electrophoresis (4) that D. radiodurans contains 4 chromosomes per nucleoid in the plateau phase and 8 to 10 chromosomes during exponential growth (9).…”
mentioning
confidence: 99%